The Teaching Material of Drama Appreciation based on Project-based Learning by Interactive Multimedia-assisted - Syofiani; Hasanuddin, WS.; Syahrul, Ramadhan (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to develop teaching materials for Drama Appreciation based on project-based learning with multimedia assistance in institutions. During this time, the teaching materials used in the learning process are in the form of textbooks so that students cannot provide contextual experience. This study is a research development using the ADDIE model, which is at the Analysis and Design stages. A needs analysis is carried out to determine the effectiveness of the Drama Appreciation teaching materials used so far in learning by giving questionnaires to lecturers and students. The results of the analysis showed that both lecturers and students expected the development of teaching materials for Drama Appreciation courses. While the design stage is designing Drama Appreciation teaching material development based on the findings of the needs analysis. The design of teaching materials uses multimedia-assisted project-based learning (PjBL) stages. The design was developed in the form of multimedia-assisted teaching materials using Macromedia Flash 8, lecturer manuals, student manuals, and model books. Products that are produced go through stages of validation by material experts, linguists, and IT experts.